The Protection Of Educational Rights For Child Labour - Khairatunnisa Khairatunnisa; M. Ya’kub Aiyub Kadir (Fakultas Hukum Universitas Syiah Kuala, 2019)
Indonesia has been ratified UNCRC through a Presidential Decree No. 36 of 1990. Meanwhile, under article 68 of Law No. 13 of 2003 on Labour, provide the prohibition of the employer from employing the children, with the exception in article 69.. In Central Aceh, it is become a habit for horse owners to hire children.This paper aim to find the protection of educational rights for child labour in Indonesia generally according to International Human Rights Instruments; and the protection of child labour especially in case of Child Labour at Horse Stable in Takengon, Central Aceh.The research use normative empirical approach. The result found the protection of educational rights have been stated in several International Human Rights Instruments; and it is the duty of government along with family toward the protection of educational rights for child labour. It is suggested to the Indonesian government to create a monitoring body that focus on Child Labour issue. The government of Central Aceh should make local regulation regarding the educational rights for child labour.